2004
DOI: 10.1159/000082078
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose Fermentation by <i>Saccharomyces cerevisiae</i> Lacking Hexose Transport

Abstract: Sucrose is the major carbon source used by Saccharomyces cerevisiae during production of baker’s yeast, fuel ethanol and several distilled beverages. It is generally accepted that sucrose fermentation proceeds through extracellular hydrolysis of the sugar, mediated by the periplasmic invertase, producing glucose and fructose that are transported into the cells and metabolized. In the present work we analyzed the contribution to sucrose fermentation of a poorly characterized pathway of sucrose utilization by S.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
10

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 86 publications
(43 reference statements)
2
45
0
10
Order By: Relevance
“…The main roles of glycerol are in the reoxidation of NADH produced by anabolic metabolism and the regulation of osmotic pressure in the presence of high sugar concentrations and other stressors such as SO 2 (Ugliano and Henschke, 2009). During the first two days of fermentation, the hydrolysis of sucrose by yeast invertase increased the concentration of fructose and glucose, which could cause osmotic pressure and rapidly increase the concentration of glycerol (Batista et al, 2005). On the other hand, some amino acids such as proline could serve as osmoprotectants, thus reducing the need for glycerol formation (Takagi, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The main roles of glycerol are in the reoxidation of NADH produced by anabolic metabolism and the regulation of osmotic pressure in the presence of high sugar concentrations and other stressors such as SO 2 (Ugliano and Henschke, 2009). During the first two days of fermentation, the hydrolysis of sucrose by yeast invertase increased the concentration of fructose and glucose, which could cause osmotic pressure and rapidly increase the concentration of glycerol (Batista et al, 2005). On the other hand, some amino acids such as proline could serve as osmoprotectants, thus reducing the need for glycerol formation (Takagi, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Standard methods for yeast transformation, DNA manipulation, and analysis were employed (2). The AGT1 gene was deleted according to a previously described PCR-based gene replacement procedure (4). Briefly, the kanMX6 cassette from plasmid pFA6a-kanMX6 (26) was amplified with primers AGT1-pFA6-F1 and AGT1-pFA6-R1, and the resulting PCR product of 1,579 bp was used to transform competent yeast cells.…”
Section: Methodsmentioning
confidence: 99%
“…The molecular identity of maltotriose transporters in S. cerevisiae remained largely unknown until some years ago when a new permease gene, designated AGT1, in a partially functional mal1g locus was characterized (16). The AGT1 H ϩ symporter transports a series of ␣-glucosides (35) and has high affinity (K m , ϳ8 mM) for trehalose and sucrose and significantly lower affinity (K m , ϳ20 to 35 mM) for maltose, maltotriose, and ␣-methylglucoside (1,4,32,33). In accordance with the importance of maltotriose transport for the industrial application of yeasts, practically all brewing strains have the AGT1 permease gene in their genomes, and transcriptome studies have also shown high levels of expression of this gene during wort fermentation (19,20,23,39).…”
mentioning
confidence: 99%
“…Os genes HXT diferem entre si quanto à regulação transcricional e pós-transcricional, especificidade de substrato e afinidade por glicose (BATISTA et al, 2004;KUYPER et al, 2006). As diferenças nas cinéticas das proteínas …”
Section: S Cerevisiae (Gardonyi E Hahn-hägerdal 2003a) Ao Contráriunclassified